Gambaran Gaya Hidup Penderita Hipertensi di Masa Pandemi Covid-19 - Susilawati; Gamya Tri Utami; Bayhakki (HEALTH CARE: JURNAL KESEHATAN, 2022)
People's lifestyles during the pandemic are leaning towards risky lifestyles. The purpose of this research is to identify the lifestyle of people with hypertension during the COVID-19 pandemic in Rejosari Public Health Center, Tenayan Raya District, Pekanbaru City. This research used a quantitative descriptive design. The research sample were 83 respondents who were taken based on the inclusion criteria using purposive sampling technique. The analysis used is univariate analysis. The result of this research is there were 60 respondents who had low physical activity (72.3%), 76 respondents had poor eating and drinking habits (91.6%), 71 respondents did not smoke (85.5%), and 73 respondents have stress levels in the normal category (88%). Overall, the respondents' lifestyles during the COVID-19 pandemic showed poor behavior.